Nursing Care for Management of Hold Relax to Reduce Pain in Elderly with Osteoarthritis at Ikedaen Hospital Japan - Afifah, Siti Nur; Jati, Riani Pradara (Global Health Science Group, 2024)
Ostearthritis, a type of arthritis that often occurs in the elderly, is a degenerative disease, which is chronic. One way to treat osteoarthritis in the elderly is to carry out osteoarthritis therapy by doing joint movement exercises, one of which is Hot Relax. This scientific research aims to find out the effectiveness of Hot Relax therapy exercises to reduce pain. This scientific study uses a nursing care approach method that applies Hot relax exercise therapy. This Hot Relax therapy exercise method is carried out 3 days in a row for 20 minutes every day. As a result of Hold Relax therapy exercises, patients experienced a reduction in pain and were able to carry out activities even with a little help.